2021
DOI: 10.1038/s41598-021-98773-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in hospitalized patients with COVID-19 and its incremental value in outcomes prediction

Abstract: Recent reports linked acute COVID-19 infection in hospitalized patients to cardiac abnormalities. Studies have not evaluated presence of abnormal cardiac structure and function before scanning in setting of COVD-19 infection. We sought to examine cardiac abnormalities in consecutive group of patients with acute COVID-19 infection according to the presence or absence of cardiac disease based on review of health records and cardiovascular imaging studies. We looked at independent contribution of imaging findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(30 reference statements)
0
7
1
Order By: Relevance
“… 24 Systolic measures, including both LVEF and GLS, have been shown to be associated with troponin, 25 and GLS has been shown to add prognostic information beyond presence of cardiac injury and clinical characteristics. 26 , 27 This previously observed additive clinical benefit of echocardiography contrasts with our findings and may rely on the prior studies being retrospective, with echocardiograms being performed clinically and, hence, subject to indication bias. The strength of a prospective study as ours is that it includes a broader scope of patients with COVID‐19, providing more unselected insights as to the pathophysiological features of cardiac injury and myocardial dysfunction.…”
Section: Discussioncontrasting
confidence: 98%
“… 24 Systolic measures, including both LVEF and GLS, have been shown to be associated with troponin, 25 and GLS has been shown to add prognostic information beyond presence of cardiac injury and clinical characteristics. 26 , 27 This previously observed additive clinical benefit of echocardiography contrasts with our findings and may rely on the prior studies being retrospective, with echocardiograms being performed clinically and, hence, subject to indication bias. The strength of a prospective study as ours is that it includes a broader scope of patients with COVID‐19, providing more unselected insights as to the pathophysiological features of cardiac injury and myocardial dysfunction.…”
Section: Discussioncontrasting
confidence: 98%
“…Other publications have dealt with the prevalence and clinical impact of pericardial effusion in acute COVID‐19 infection. 6 , 8 , 9 , 10 However, all these reports were either retrospective or based on systematic literature review, assessing only patients with clinically indicated echocardiographic examinations. Our study used a prospectively defined protocol and included unselected hospitalized patients encompassing all grades of disease severity, which can better evaluate the prevalence and clinical impact of pericardial effusion in hospitalized patients with COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Diastolic dysfunction occurred in 20%, and RV systolic dysfunction was noted in 18%. 6 Cardiac monitoring using clinical, laboratory, and imaging parameters can be used to help risk stratify patients with COVID‐19. 2 , 5 , 7 However, most reports on cardiac involvement focus on myocardial involvement, and reports describing pericardial disease are less common, mostly retrospective or based on systematic literature review, assessing only patients with clinically indicated echocardiographic examinations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CMR studies evaluating patients recovered from COVID of variable severity have generally found preserved LVEF, but a small decline in RVEF compared with controls. [43][44][45]89 A more recent, larger study exclusively focusing on hospitalized patients with COVID, however, demonstrates an increased risk of impaired LVEF in convalescence among those who had elevated troponin levels while hospitalized compared to both matched controls and patients with COVID without elevated troponin during hospitalization. 51 Many questions remain regarding the underlying risk factors and the impact of severity and subtype of infection for the development of COVID-related secondary ventricular dysfunction.…”
Section: Secondary Ventricular Dysfunctionmentioning
confidence: 99%